Mangosteen rind ethanol extract’s mechanism of action against SGLT-2 receptors: In silico and in vivo - Rifa’atul Mahmudah, Elin Yulinah Sukandar, I Ketut Adnyana (Journal of Applied Pharmaceutical Science, 2024)
It is believed that the ethanol extract of mangosteen rind (EEMR) with the marker compounds alpha-mangostin, gamma-mangostin, and xanthone can be used for diabetes mellitus (DM) treatment. The research was conducted on the SGLT-2 receptor to determine the mechanism of action of EEMR. As a new treatment option for DM, this receptor has emerged as one of the most promising targets. The study was conducted using two methods: in silico and in vivo. In the in silico method, the binding of alpha-mangostin, gamma-mangostin, and xanthone ligands to the SGLT-2 receptor was observed through molecular docking and molecular dynamic simulation. Meanwhile, in vivo, using male Wistar rats as test animals, the work of EEMR in treating DM was observed by the antihyperglycemia parameter and its effect on SGLT-2 expression through RT-qPCR and enzyme-linked immunosorbent assay (ELISA) methods. Statistically, the test results were considered significant (p < 0.05) using the two-way ANOVA analysis method, Tukey’s post hoc. The results showed that alpha-mangostin was the ligand/compound with the best binding to the SGLT-2 receptor. While in the form of an extract, EEMR was able to show significantly different antihyperglycemic effects (p < 0.05) than the control group at all doses (100, 200, and 400 mg/kg bw rat) in the 4th week of observation. In addition, EEMR could also decrease SGLT-2 gene expression, which was seen through the RT-qPCR method and was confirmed by the administration of EEMR at doses of 200 and 400 mg/kg bw rat and also decreased SGLT-2 protein expression in ELISA method observations at all test doses. EEMR’s ability to decrease SGLT-2 expression makes it a viable treatment option for DM. The compound alpha-mangostin is expected to play a major role in this process.
Keywords: Ethanol extract of mangosteen rind, diabetes mellitus, SGLT-2, in silico, in vivo